Percutaneous transpapillary biliary stent placement for distal malignant biliary obstruction: Outcomes and survival analysis - Zu, Qing-Quan; Zhang, Jin-Xing; Wang, Bin; Ye, Wei; Liu, Sheng; Shi, Hai-Bin (Turkish Journal of Gastroenterology, 2019)
Background/Aims: For distal malignant biliary obstruction (MBO), a percutaneous metal stent is usually inserted by the transpapillary method. However, stent-related complications and recurrent biliary obstruction following transpapillary stent placement are concerns, and survival analysis of patients with distal MBO has rarely been done. Materials and Methods: From January 2012 to March 2016, 104 patients underwent transpapillary uncovered metal stent placement for distal MBO at our institution. Clinical success, complications, recurrent biliary obstruction rates, and predictors of survival were analyzed. Results: Of the total 104 patients, clinical success after stent insertion was achieved in 93 patients (90.3%). Major complications were observed in 24 patients (23.1%), which were as follows: cholangitis in 19 patients; pancreatitis in four patients; and biloma in one patient. Recurrent biliary occlusion was observed in 28 patients (26.9%). The median overall survival period was 162 days. The 3-, 6-, and 12-month overall survival rates after stent insertion were 64.4%, 41.3%, and 10.6%, respectively. Results of multivariate analysis indicated that metastatic carcinoma compared with ampullary carcinoma (HR=3.82; 95% CI, 1.30-11.24; p=0.015) and longer biliary stricture (HR=1.04; 95% CI, 1.02-1.06; p<0.001) were independent risk factors for worse survival after metal stent insertion. Conclusion: Transpapillary stent placement was found to be effective with acceptable complication rates for treating distal MBO. Primary tumor and length of biliary stricture were found to be statistically significant independent prognostic factors for survival.